Assessment of the vitamin D status and its determinants in young healthy students from Palestine - Janina Susann Lenz; Nathan Tintle; Felix Kerlikowsky; Manal Badrasawi; Rana Zahdeh; Radwan Qasrawi; Andreas Hahn; Jan Philipp Schuchardt (Journal of Nutritional Science, 2023)
The global prevalence of vitamin D deficiency is high. Poor vitamin D status, especially in women, has been reported in several countries in the Middle East despite adequate year-round sunlight for vitamin D synthesis. However, data on vitamin D status in Palestine are scarce. The aim of this cross-sectional study was to evaluate vitamin D status based on serum concentrations of 25-hydroxycholecalciferol [25-(OH)D] among young healthy Palestinian students (18–27 years) and to assess associations between 25-(OH)D concentrations and several predictors. The mean 25-(OH)D concentration of women (n 151) was 27⋅2 ± 14⋅5 nmol/l, with the majority having insufficient (31⋅1 %) or deficient (<60 %) 25-(OH)D status. Only 7 % of women achieved sufficient or optimal 25-(OH)D status. In contrast, men (n 52) had a mean 25-(OH)D concentration of 58⋅3 ± 14⋅5 nmol/l, with none classified as deficient, and most obtaining sufficient (55⋅8 %) or even optimal 25-(OH)D status (11⋅5 %). Among women, 98 % wore a hijab and 74 % regularly used sunscreen. Daily dietary vitamin D intake (3-d 24-h recalls) was 45⋅1 ± 36⋅1 IU in the total group (no sex differences). After adjustment, multiple linear regression models showed significant associations between 25-(OH)D concentrations and the use of supplements (B = 0⋅069; P = 0⋅020) and dietary vitamin D (B = 0⋅001; P = 0⋅028). In gender-stratified analysis, the association between supplement use and 25-(OH)D concentrations was significant in women (B = 0⋅076; P = 0⋅040). The vitamin D status of women in the present cohort is critical and appears to be mainly due to wearing a hijab, regular use of sunscreen and low dietary vitamin D intake. The vitamin D status of the women should be improved by taking vitamin D containing supplements or fortified foods.